Emotional state as correlates to self-esteem among deaf in Philippine School for the Deaf - Jake Ryan A. Canlas. 4 0 16; 5 (2019)
ABSTRACT: The research aimed to know the emotional state of deaf and correlation to self- esteem. The research aims to answer three questions: (1) What is the level of emotional states among the respondents in terms of depression, anxiety, stress? (2) What is the level of self-esteem among the respondents in terms of low level of self-esteem, average level of self-esteem, and high level of self-esteem? (3) Is there significant relationship between emotional states and self-esteem among the respondents? The researcher used the standardized scale the Rosenberg and D.A.S.S scale, a 4 point likert scale. Self-esteem refers to the extent to which we accept or approve of ourselves or how much we value ourselves and it always involves a degree of evaluation, self-esteem is either positive or negative. Emotional state is the state of a person's emotion, and state of arousal characterized by alteration of feeling tone by physiologic behavioral changes. Under of emotional state are depression, anxiety, and stress.
Umdergraduate Thesis: (B.S Psychology)- Pamantasan ng Lungsod ng Maynila, 2019.
Keywords: 2 -- 0; 6; 20; 20; 2